2020
DOI: 10.1002/anie.202006822
|View full text |Cite
|
Sign up to set email alerts
|

In Cellulo Protein Semi‐Synthesis from Endogenous and Exogenous Fragments Using the Ultra‐Fast Split Gp41‐1 Intein

Abstract: Protein semi‐synthesis inside live cells from exogenous and endogenous parts offers unique possibilities for studying proteins in their native context. Split‐intein‐mediated protein trans‐splicing is predestined for such endeavors and has seen some successes, but a much larger variety of established split inteins and associated protocols is urgently needed. We characterized the association and splicing parameters of the Gp41‐1 split intein, which favorably revealed a nanomolar affinity between the intein fragm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…Our experiences with bead‐loading for protein transduction showed that this technique is inexpensive, rapid and very simple to implement for well‐adherent cells. However, some cells will be lost during the procedure due to detachment and the protein delivery is difficult to control in terms of percentage of cells transduced (20 to 50 %) and intracellular protein concentration [12c] . Of note, these observations on the particular cellular delivery method do not affect our conclusions on the intracellular use of photobodies.…”
Section: Figurementioning
confidence: 92%
See 1 more Smart Citation
“…Our experiences with bead‐loading for protein transduction showed that this technique is inexpensive, rapid and very simple to implement for well‐adherent cells. However, some cells will be lost during the procedure due to detachment and the protein delivery is difficult to control in terms of percentage of cells transduced (20 to 50 %) and intracellular protein concentration [12c] . Of note, these observations on the particular cellular delivery method do not affect our conclusions on the intracellular use of photobodies.…”
Section: Figurementioning
confidence: 92%
“…[8a] For the intracellular delivery of purified photobodies, we pursued the bead-loading technique, because it is easily and quickly performed without the need for any specialized equipment. [12] To this end, small glassbeads and the photobody or nanobody protein (25 μM) were added to HeLa cells, protein uptake was enforced by sharply hitting the culture dish on the bench (8 ×) and cell recovery was allowed for 2 min before washing.…”
mentioning
confidence: 99%
“…Recently, Mootz and co-workers reported on the Gp41-1 split intein and in cellulo semisynthesis of intracellular proteins in live mammalian cells using relatively short peptide fragments (N-intein: 88 aa, C-intein: 37 aa). [97] This split intein displays rapid PTS (t 1/2~5 s at 37°C) with high yields. [174,175] However, split intein approaches are still limited to rather big POI modifications for efficient labeling, when targeting the N terminus of proteins like GPCRs and RTKs.…”
Section: Figure 12mentioning
confidence: 95%
“…[96] Covalent modification: pre-incubation with 0.5 mM TCEP prior to addition of the labeling probe (0.5 μM) at room temperature. [95] Split intein [97] Gp41-1 system: N-intein, 88 aa; C-intein, 37 aa…”
Section: Labeling Approachmentioning
confidence: 99%
See 1 more Smart Citation